Quand l’exploitation mémorielle officielle des archives conduit à redécouvrir les fonds : le cas de l’enregistrement filmé du général de Gaulle du 2 juillet 1940 - Violaine Challéat-Fonck (Conserveries Mémorielles)
In charge of preservation, commercial and cultural diffusion of the cinematographic and photographic heritage of the Ministry of Defence, ECPAD contribute towards the national ceremonies of commemoration. In this domain, archives are henceforth frequently convened to strengthen the solemnity of the moment. The preparation of these demonstrations allows to bend again over historic collections to select the most symbolic images. In this occasion, the documentary knowledge of Archives collections can be improved, as shown by the example developed here, concerning a filmed recording of the general de Gaulle, dated 1940.